Alcohol consumption and risk of multiple myeloma in the NIH‐AARP Diet and Health Study. Issue 1 (30th October 2018) - Santo, Loredana; Liao, Linda M.; Andreotti, Gabriella; Purdue, Mark P.; Hofmann, Jonathan N.
Abstract : The epidemiologic evidence regarding the relationship between alcohol consumption and multiple myeloma (MM) risk remains limited and inconsistent, although recent studies suggest a potential protective effect. We prospectively investigated the risk of MM in relation to alcohol consumption frequency among 499, 292 participants enrolled in the National Institutes of Health (NIH)‐AARP Diet and Health Study in 1995–1996. A total of 1, 312 MM cases were identified during follow‐up through December 2011. Hazard ratios (HR) and 95% confidence intervals (CI) for categories of alcohol consumption relative to those defined as light drinkers (<1 drink/week) were estimated using multivariate Cox proportional hazard models. Overall, increasing frequency of alcohol consumption was inversely associated with MM ( p ‐trend = 0.01), with a statistically significant association among those who consumed 2 drinks per day (HR = 0.70, 95% CI: 0.50, 0.98); similar but not statistically significant associations were observed for greater frequency of alcohol consumption. Among women, risk of MM was reduced among those who consumed less than one drink per day (HR = 0.73, 95% CI: 0.56, 0.97) and associations with greater frequency of alcohol consumption were inverse although not statistically significant. The findings of this large prospective investigation suggest that moderate alcohol consumption may be associated with reduced future risk of MM. Abstract : What's new? While alcohol consumption is a risk factor for multiple cancer types, epidemiological studies examining specific associations with multiple myeloma have yielded inconsistent results. Here, the authors investigated relationships between alcohol consumption and multiple myeloma risk using data for nearly half‐a‐million adults enrolled in the National Institutes of Health‐AARP Diet and Health Study. Analyses reveal a significant association between reduced multiple myeloma risk and moderate drinking, defined as 2 to 2.9 drinks per day. Further investigation is needed to better understand how alcohol consumption influences multiple myeloma risk.